Perceptions of School Management Transformation in Guangdong Province: Between Digital Reform and Administrative Persistence - Huang Kuidong; Amrozi Khamidi; Ainur Rifqi (Journal of General Education and Humanities, 2026)
School management transformation has become a central issue in educational modernization, yet descriptive evidence on how this transformation is perceived in Guangdong Province remains limited. This study aims to examine perceptions of school management transformation across six dimensions embedded in the research instrument: Traditional Limitations, Value Transformation, Teacher Development, Collaborative Governance, Digital Transformation, and Regional Collaboration. The study employed a quantitative descriptive survey design using a 30-item questionnaire with a five-point Likert scale administered directly to respondents in the field. The analysis was based on 38 valid responses. Because respondent role categories were not recorded in the final tabulated records, the findings are interpreted as descriptive perceptions rather than as representative evidence of a clearly defined stakeholder group. The results show that Digital Transformation and Regional Collaboration received the highest dimension-level mean scores, while Traditional Limitations also remained relatively high, indicating that reform-oriented perceptions coexist with continued recognition of administrative persistence. At the item level, the strongest support was found for data-informed school leadership and inter-regional sharing of management experience. In contrast, lower scores were observed on items related to protecting students’ educational rights, integrating local resources, and the practical use of regional policy opportunities. Overall, the findings suggest that school management transformation in Guangdong is perceived as meaningful but still incomplete.